2022
DOI: 10.1371/journal.pone.0266029
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the psychological mechanisms of return to sports readiness after anterior cruciate ligament reconstruction

Abstract: Purpose The psychological response to an Anterior Cruciate Ligament (ACL) injury is significant and can negatively impact return to sports outcomes. This study aimed to quantify the association between factors associated with return to sport using network analysis. Methods 441 participants who underwent primary ACL reconstruction. The 12-item ACL Return to Sport after Injury (ACL-RSI) scale was administered to all participants 12 months after surgery. Three network analyses were used to quantify the adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…However, this is a common area of research in other sport-related knee injuries, such as anterior cruciate ligament tears. 2,15 Our data suggest that orthopaedic trauma populations may benefit from further research in this area and targeted interventions.…”
Section: Discussionmentioning
confidence: 82%
“…However, this is a common area of research in other sport-related knee injuries, such as anterior cruciate ligament tears. 2,15 Our data suggest that orthopaedic trauma populations may benefit from further research in this area and targeted interventions.…”
Section: Discussionmentioning
confidence: 82%
“…However, a recent network analysis of the psychological contributors to the ACL-RSI score concluded that the fear of reinjury and being relaxed about playing sports explained most of the variation in psychological readiness to RTS at 1 year after ACLR. 35 The fear of reinjury, potentially along with other psychological factors not explored in the current study, such as motivation and knee confidence, 43,53,57 may, therefore, be the primary drivers of psychological readiness to RTS, whereas physical function may contribute to a lesser extent.…”
Section: Discussionmentioning
confidence: 84%
“…Work by Ardern et al noted that as few as 55% of patients after ACLR return to preinjury level of activity 48 . Factors often linked to patients electing to not return to activity include fear of reinjury, inadequate psychological readiness to RTS, lack of confidence 55 . Recent work has investigated the opportunity to infuse psychologically informed care throughout the rehabilitation process to assist with the factors as patients progress through their postsurgical acute phase of rehabilitation 56,57 .…”
Section: Booster Visits: a Brief Overviewmentioning
confidence: 99%